High Gain Cascaded Low Noise Amplifier using T-Matching Network - Othman , A. R; Hamidon , A. H; Abdul Wasli. , C; Ting , J. T. H; Mustaffa , M. F; Ibrahim , A.B (JTEC, 2010)
This project presents a design of high gain cascaded low noise amplifier (LNA), which operates at 5.8 GHz frequency for WiMAX application. The LNA designed used T-matching network consisting of lump reactive elements and microstrip at the input and the output matching load uses quarter wavelength techniques. A cascaded LNA is developed in this project contribute a high gain of 36.8 dB with overall noise figure of 1.3 dB. The overall measured bandwidth measures is 1.240 GHz with S parameters S11, S12 and S22 measured are -11.4dB, -39.1dB and -12.3dB respectively. The input sensitivity of the LNA is -80dBm which compliant with the IEEE 802.16 WiMAX application. The LNA used FET transistor FHX 76 LP from Eudina Inc.